Pricing and performance of Nordic initial public offerings - Hietikko, Pauli (2021)
Initial public offerings (IPO) have been topic of interest in the field of finance for quite some time. Center of interest has revolved in pricing of IPOs, performance in short and longer run and why companies want to go public. Earlier research has provided evidence from around the world that IPOs are generally underpriced and short and long run performance over benchmark index is usually negative. Research on initial public offerings has been thorough in the past trying to capture the phenomenon of IPOs from many angles. This thesis provides more recent results how Nordic IPOs are priced and aims to fill existing gap in the IPO research by observing whether so called size effect where smaller companies outperform larger companies, exists in Nordic IPOs stocks or not. The companies are main market listed companies in Sweden, Finland, Denmark, and Iceland from time period of 2010-2017. The performance of Nordic IPOs is observed from periods of one day up to two years. The study also evaluates whether the first day return has any implications for performance after the IPO. Size effect in IPOs has not been studied according to my knowledge and for that reason it is interesting addition to existing IPO research. Theory part of this thesis focuses on theories explaining why companies want to go public, what are pros and cons of it and why IPOs are often valued as underpriced. Theories explain reasons for going public from practical point of view. Literature review after the theory part will show results from academic research of underpricing of IPOs, how newly listed companies perform on short and longer run and evidence of size effect. The main findings from of this thesis is that Nordic IPOs from Finland, Sweden, Denmark, and Iceland have been underpriced 2010-2017, large cap IPOs had the highest initial return from the first trading day, small cap and underpriced IPOs had the best performance in longer run. Size effect seems to exist on Nordic IPOs. Pörssilistautumiset ovat olleet rahoitustutkimuksen ...